International currency in the postwar history of the world monetary system. Theory and practice - Bilski, Janusz (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
This article aims to discuss the idea of nature, forms and mechanisms of international currency. It presents the evolution of the main forms of global currency. Furthermore the benefits and risks coming from the currency seigniorage are studied.